ANALISA KEBUTUHAN AIR BERSIH TERHADAP EFEKTIVITAS PELAYANANAN DAN KUANTITAS PELANGGAN PADA PERUSAHAAN DAERAH AIR MINUM TIRTA AGARA KUTACANE ACEH TENGGARA - Sabitah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
The Regional Drinking Water Company TirtaAgaraKutacane, having its address at Jln Jend. A. Yani No. Kutacane Aceh Tenggara is the object of research, while the subject is the quantity of customers. In this study, the background of the problem is whether there is a quantity of PDAM TirtaAgara customers, and whether it has been effective in providing services to customers. This study aims to analyze the need for clean water, service effectiveness and customer quantity at PDAM TirtaAgaraKutacane. This research is descriptive qualitative, the method of collecting data is field research using direct observation and interview methods on the research object to obtain an overview of the research subject.